Setting Research Agendas for Animal Science - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Proceedings of the symposium on Food, Lands and Livelihoods, organised in Nairobi, Kenya, in January 1998 (see Spore 75, p. 13).British Society of Animal Science®¢CTA copublication. 1998. BSAS Occasional Publication Series number 21. 138 pp.ISBN 0...